Konsep Ilmu Menurut Hamka dan Implikasinya Terhadap Kurikulum Pendidikan Islam - Coil, Coil; Aprison, Wedra; Wati, Salmi; Husni, Arman (Indonesian Research Journal on Education, 2023)
This research is motivated by the importance of the position of science in human life which is one of the basic human rights. Knowledge gained in the educational process is a primary need that must be obtained by every human being. With the knowledge it will increase the degree of human beings. Islam is very concerned about science, because with science humans can work and achieve. The purpose of this study was to find out Hamka's view of science and its implications for the Islamic education curriculum. This type of research is Library Research which is a descriptive research. The method used to analyze the data is Content analysis, which explores Hamka's view of the concept of science and its implications forthe Islamic education curriculum. After conducting an in-depth study, the results showed that the concept of science according to Hamka is the equivalent of knowledge that includes general science and religion, and to achieve this process science must be based on faith and then put it into practice. Science is not only to help humans earn a decent living, but more than that, with knowledge humans will be able to know their God, form their morals, and always seek the pleasure of Allah. The implication of the concept of Science on the Islamic education curriculum according to Hamka is that science must cover all sciences without separating general science and religious knowledge. According to Hamka, the educational materials contained in the Islamic education curriculum consist of at least: monotheism,interpretation, fiqh, hadith, nahwu, mantiq, bayan, history, philosophy, literature, arithmetic, earthscience, astronomy, body and soul science. human, social science, plant science, government science, archery skills, swimming, and horse riding, and others.